the analysis of methodological significant strategies in the development of the oral communication of the english language in the students at octavo año A de educacion general basica at unidad educativa “nidia jaramillo, riobamba city, chimborazo province, in the academic term october 2016-march 2017. - Remache Tixe, Alex Javier (2018)
Speaking is one of the most important skills to be developed in an effective communication, for this is fundamental to integrate communicative methods as a teaching strategy allowing to the students feel motivated to support their ideas, interchange information in naturally and spontaneously way creating communicative situations. This approach is a relatively stable indicator of how teachers use different methodology and how the students respond developing oral communication skills. In this project different methodological strategies were observed to determine whether students of Octavo Año “A” de Educación General Básica at the Unidad Educativa “Nidia Jaramillo”, City of Riobamba, Chimborazo Province, in the academic term October 2016 – March 2017, developed oral activities helped by the teacher. This research had worked with a population of 21 students and 1 teacher. It had an exploratory level, therefore qualitative method was used to study the population directly using the observation as an instrument helped of its technique such as: observational guide, in order to know how teacher applied communicative tasks connected with student’s behavior to practice language in an accuracy and proficiency way. Analysis and interpretation of the results was performed, in which we observed and analyzed the activities that students performed. Finally, it was determined that teacher did not apply correctly the methodological strategies with the students; who at the moment to participate in role plays, question and answer, oral and group lessons, oral picture descriptions, games and songs did not develop their self- oral confidence in the English teaching and learning process.